THE EFFECT OF STEAM ORIENTED INQUIRY BASED LEARNING MODEL ON CRITICAL THINKING SKILLS AND COGNITIVE LEARNING OUTCOMES ON BIODIVERSITY - Alda Alfina; Sofia Ery Rahayu; Zahra Nugraheni (INSECTA: Integrative Science Education and Teaching Activity Journal, 2026)
This study investigated the effect of the STEAM-oriented Inquiry Based Learning (IBL) model on students’ critical thinking skills and cognitive learning outcomes in biodiversity topics among tenth-grade students at SMA Laboratorium UM. The study employed a quasi-experimental design using a Nonequivalent Control Group Design and involved 102 students divided into three groups: a STEAM-oriented IBL class, an IBL class, and a conventional learning class. Data were collected through tests measuring critical thinking skills and cognitive learning outcomes. The analysis techniques included ANCOVA, Bonferroni post hoc tests, and N-Gain analysis. The findings showed that the STEAM-oriented IBL model significantly influenced students’ critical thinking skills and cognitive learning outcomes, with significance values of p < 0.001. The effect sizes were high, with η² values of 0.734 for critical thinking skills and 0.742 for cognitive learning outcomes. Furthermore, the N-Gain analysis indicated substantial improvement in both variables, with scores of 0.9 for critical thinking skills and 0.8 for cognitive learning outcomes. Overall, the STEAM-oriented IBL model proved more effective than the IBL and conventional models in improving students’ higher-order thinking skills and academic achievement in biodiversity learning. The implementation of STEAM elements within the Inquiry Based Learning process encouraged students to participate actively in problem solving, investigation, collaboration, and knowledge construction. This approach also provided learning experiences that supported conceptual understanding and strengthened students’ ability to analyze, evaluate, and interpret biological concepts in real-life contexts. Therefore, the STEAM-oriented IBL model can be considered an effective and innovative learning strategy for secondary biology education.